THE RESISTANCE OF CHILLI (Capsicum annuum L.) FROM SEEDS INDUCED BY 0.2 mT MAGNETIC FIELD AND INFECTED BY Fusarium oxysporum - Feni Kaisah; Rochmah Agustrina; Eti Ernawiati; Martha L. Lande; Lili Chrisnawati (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2021)
Red chili pepper (Capsicum annuum L.) is one of the most widely cultivated commodities in Indonesia. However, until now the production was never covering the public’s demand. Red chili pepper plants are susceptible to disease caused by the infection of Fusarium oxyporum (Fox) fungi, causing a decrease in plants’ production. Fungicide usage to control Fox can cause plants’ resistance to the pathogen. The eco-friendly way to control Fox could be achieved by utilizing a magnetic field. This research arranged using Completely Randomized Design (CRD) with the combination between 0,2 mT magnetic field induction and Fox infection consist of control (M0); 0,2 mT magnetic field induction for 7 minutes and 48 seconds (M7); and 15 minutes and 36 minutes (M15); as well as seed infection with Fusarium oxyporum that consist of control without infection (F0) and infected for 60 minutes (F60). Each test unit was repeated 5 times.